2006
DOI: 10.1086/503034
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bacteremia Using TREAT, a Computerized Decision-Support System

Abstract: Using variables available at the time that blood cultures were performed, the TREAT system successfully stratified patients on the basis of the risk for bacteremia. The system's predictions were stable in 3 locations. The TREAT system can define a low-risk group of inpatients with suspected sepsis for whom blood cultures may not be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 26 publications
0
39
1
Order By: Relevance
“…Previously described BDSSs for infectious diseases other than VAP considered choosing empirical therapy for bacterial infections [21], predicting the pathogens of bacteraemia originating from the urinary tract and from other sites [22][23][24], and diagnosing community-acquired pneumonia (CAP) [25]. This BDSS for diagnosing CAP was retrospectively evaluated in 41,371 patients that had visited an emergency department and for which a discharge diagnosis was known.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described BDSSs for infectious diseases other than VAP considered choosing empirical therapy for bacterial infections [21], predicting the pathogens of bacteraemia originating from the urinary tract and from other sites [22][23][24], and diagnosing community-acquired pneumonia (CAP) [25]. This BDSS for diagnosing CAP was retrospectively evaluated in 41,371 patients that had visited an emergency department and for which a discharge diagnosis was known.…”
Section: Discussionmentioning
confidence: 99%
“…The present analysis included all CAP patients treated empirically with a combination of a b-lactam and a macrolide or with a b-lactam antibiotic alone, participating in the TREAT study [19,20], a system for balancing antibiotic treatment against development of drug resistance. Patients were enrolled as part of a two-phase study (observational and interventional) designed to evaluate the effectiveness of TREAT, a computerised decision support system for antibiotic treatment of common bacterial infections among in-patients (Clinical-Trials.gov Identifier: NCT00233376).…”
Section: Methodsmentioning
confidence: 99%
“…The use of dynamic Bayesian networks as the basis for the construction of prognostic models has been explored in [34] with the particular application to prognosis of low-grade carcinoid tumours; evaluation results regarding three patients were also presented. Another Bayesian-network-based decision-support system, called TREAT, aiming at predicting bacteremia in patients is described in [28]. A randomised clinical trial showed improvement in the percentage of appropriate empirical antibiotic treatments when using the system [29].…”
Section: Related Workmentioning
confidence: 99%